Asymptotic Properties of Instrumental Variables Statistics for Testing Non-Nested Hypotheses - Ericsson, Neil R. (Review of Economic Studies, 1983)
This paper develops Instrumental Variables statistics for testing non-nested hypotheses when the hypotheses considered are single equations from a system of linear dynamic simultaneous equations. Asymptotic distributions of those statistics and of comparable Maximum Likelihood statistics are derived under the null hypothesis, a local non-nested alternative hypothesis, and a local “comprehensive” alternative hypothesis. The asymptotic powers of the non-nested hypothesis tests are compared with those of tests of nested hypotheses, and a numerical application is given.